Risk analysis and phytosanitary measures to prevent the introduction of the quarantine pest Huanglongbing (HLB) of citrus into Ecuador (Agroindustrial Science, 2026)
Citrus Huanglongbing (HLB) is considered the most devastating disease of citrus plants because of the damage it causes, its difficulty in diagnosis, and its speed of dissemination, mainly due to the international trade in plant propagation material and its vectors Diaphorina cilri and Trioza erylreae. Nowadays, there is no effective treatment for HLB, so early detection is necessary to mitigate its spread to eradicate infected trees. In 2016, Colombia confirmed the presence of HLB in its territory, so there is a need to prepare this research to determine the risk level and the options for adequate phytosanitary measures to exclude the introduction of the HLB to Ecuador; the study with documentary bibliographic methodology uses an adaptation to "Work Guide for the preparation of Pest Risk Analysis (PRA) studies per Pest" established by "Agrocality" under Resolution 0002 of January 03, 2020, which comprises three stages supported by scientific-technical information that allowed to identify a high-risk level of introduction of HLB to Ecuador and the options of phytosanitary measures to avoid the introduction and dispersion of HLB; among these are the prohibition of importing citrus propagating material from countries with HLB, production of certified plants, strengthening border control s,  to control the vector.